Bilingualism Enhances Reported Perspective Taking in Men, but Not in Women - Tarighat, Samaneh; Krott, Andrea (Frontiers in Psychology, 2021)
Bilingual speakers have often been found to be superior in taking the perspective of another person. Also, females are commonly found to have enhanced perspective taking abilities compared to males, with male perspective taking being generally more easily affected by external factors. The present study investigated whether bilingualism improves perspective taking in males more strongly than in females. In total, 108 bilingual and 108 matched monolingual adults, with equal numbers of males and females, filled in the Perspective Taking subscale of the Interpersonal Reactivity Index. While monolinguals showed the typical result of females scoring higher on perspective taking than males, scores of male and female bilinguals did not differ, with both bilingual groups scoring as high as female monolinguals. Thus, bilingualism enhanced self-reported perspective taking only in males, suggesting that male perspective taking can be enhanced through socialization.